THE DOMESTIC VIOLENCE BETWEEN CRIMINAL LAW AND MISDEMEANOR LAW IN REPUBLIC OF SRPSKA - Sladić, Ljubana (Glasnik Advokatske komore Vojvodine, 2022)
Since May 2020 in the law of the Republika Srpska, domestic violence is presribed only as a criminal offense. In the paper, the author presents arguments against the exclusive criminal incrimination of domestic violence and points out the need for it to be prescribed as a misdemeanor, with a clear line of demarcation. The paper presents the results of a survey conducted with the aim of determining the attitudes of judicial authorities regarding the incrimination of domestic violence, and presents the statistics of the Basic Court in Bijeljina in relation to this crime. Interpreting the results of the survey, it was concluded that the respondents are fully acquainted with the new solutions regarding the criminalization of domestic violence and the consequences that such solutions produce in practice. Most of them are of the opinion that it is not a good solution according to which domestic violence is prescribed only as a criminal offense, nor is it a good solution according to which the court in misdemeanor proceedings imposes urgent/protective measures, but it should be done by the court in criminal proceedings. Also, the respondents largely agree that there has been no increase in prison sentences or stricter sanctions for perpetrators of domestic violence, and they agree that such persons are usually sentenced to probation, which is confirmed by the mentioned statistics.
Keywords: domestic violence, criminal offense, misdemeanor, family member, protective measures, emergency measures